Sarcopenic Obesity: The Underlying Molecular Pathophysiology and Prospect Therapies - Meiliana, Anna; Dewi, Nurrani Mustika; Defi, Irma Ruslina; Rosdianto, Aziiz Mardanarian; Qiantori, Adziqa Ammara; Wijaya, Andi (The Indonesian Biomedical Journal, 2024)
BACKGROUND: Age contributes to body composition alteration, rises a common disorder in elderly known as sarcopenic obesity (SO), which is characterized by the combination of obesity (excess fat mass) and sarcopenia (reduced skeletal muscle mass) clinical form and function.CONTENT: The primary cause of SO is insulin resistance. Glucose transporter 4 (GLUT4) dysfunction results in impaired fatty acids oxidation. Decreased muscle mass results in lower mitochondria number and volume. Both will increase oxidative stress. Together with altered myokines in SO, oxidative stress was promoted and lead to higher M1 macrophages and failure in autophagy. The pro-inflammatory condition and dysbiosis links SO to a variety of cardiometabolic conditions, including non-alcoholic fatty liver disease, type 2 diabetes, and cardiovascular disease. The mortality, comorbidities, cardiometabolic diseases, and disability or impairment of SO is higher compare to obesity or sarcopenia alone. Some treatments have been developed for SO including adequate dietary intake, vitamin D and antioxidant supplementation, and exercises.SUMMARY: SO is more prevalent among the elderly and has a significant negative impact on their quality of life. Therefore, maintaining muscle mass and strength as well as preventing obesity should be the key goals of initiatives to support healthy aging.KEYWORDS: aging, body composition, obesity, sarcopenia, skeletal muscle, metabolic syndrome